Brachytherapy dose verification using gafchromic EBT3 film - Ismail, Nur Alya Irdina (2020)
Purpose: This study presents an evaluation of gamma analysis of Gafchromic EBT3 films as dosimetric media for dose verification of three different planning of dose distribution in HDR brachytherapy environment. Methods: Eleven of 6F of Proguide plastic catheters were sandwiched with eight slabs of 1 cm of Solid Water phantoms and two slabs of 1 cm customized acrylic phantoms. The set up was scanned by computed tomography (CT) for treatment planning purpose. Three different plan, plan A (Box), plan B (Endo) and plan C (Gyn) were planned and calculated with Oncentra brachytherapy treatment planning system (TPS) by different dwell positions activated. Measurements were conducted by irradiation of Gafchromic EBT3 film placed 1 cm above the catheters for each plan. Gamma analysis of Verisoft software with passing criteria of 3% of dose difference (DD), 3 mm of distance to agreement (DTA) and 95% level tolerance was used to compare the dose distributions between the TPS data and measured data from the EBT3 film. Result: Gamma analysis demonstrated over 90% of evaluated points passed the criteria of acceptability for plan A and plan B with passing rate of 98.6% and 96.7% respectively. Plan C which more complex shape of dose distribution showed the least agreement between TPS and measured data with passing rate of 67.4%. Conclusion: Gamma analysis evaluation showed good agreement between dose distributions calculated using TPS and measured by Gafchromic EBT3 films, thus showing the potential of using film dosimetry in brachytherapy for dose verification.